The right side of the equation can be rewritten in terms of p as 4p (4p = 4(x^2 +6) = 4x^2 +24)
Now you have (x^2 +6)^2 - 21 = 4p
Replace (x^2 +6) with p
p^2 - 21 = 4p
Subtract 4p from each side:
p^2 - 21 -4p = 0
Rewrite the expression to get p^2 - 4p -21 = 0
Answer:
x = -1
Step-by-step explanation:
2(x – 2) + 6 = 0
~Distribute left side
2x - 4 + 6 = 0
~Combine like terms
2x + 2 = 0
~Subtract 2 to both sides
2x = -2
~Divide 2 to both sides
x = -1
Best of Luck!
Answer:
1. 9
2. 10
Step-by-step explanation:
idk if those first 2 are right
Answer:
The constant term is the weights rate of change, because the formula never changes.